Iron (II) and Zinc (II) complexes of gemifloxacin mesylate: synthesis, characterization, serum binding profiling, and evaluation of antimicrobial activity - Aktar, Fahima; Hossain, Md Jamal; Sultan, Md Zakir; Rashid, Mohammad A (Journal of Bangladesh Academy of Sciences, 2022)
Gemifloxacin mesylate is a synthetic fluoroquinolone derived antimicrobial agent. Two metal complexes of gemifloxacin mesylate were synthesized viz. gemifloxacin-Fe and gemifloxacin-Zn. The formed complexes were characterized by using TLC, TGA and FT-IR spectra analyses. The formed complexes were then evaluated for antimicrobial activity. The newly formed two complexes were assessed against nine bacterial and one fungal strain, where gemifloxacin (30 µg/disc) was used as a reference standard. The new complexes showed better activity than the standard reference drug against Klebsiella pneumoniae among nine bacterial strains. But two bacterial species, Acinetobacter lwoffii and Enterococcus faecium, and the fungal strain Candida albicans showed complete resistance to the newly synthesized complexes and the reference standard. The drug protein interaction with the Bovine Serum Albumin (BSA) was also studied. The interaction mechanism was explored, suggesting that gemifloxacin and its Zn (II) complex interact with BSA via a static process while the Fe (II) complex interacts via a dynamic process and the lower Ksv value also indicated that drug -BSA complexes were formed in ground-state. J. Bangladesh Acad. Sci. 46(2); 203-211: December 2022